If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9C = 72WHATISC Solving 9C = 72ACHISTW Solving for variable 'C'. Move all terms containing C to the left, all other terms to the right. Add '-72ACHISTW' to each side of the equation. -72ACHISTW + 9C = 72ACHISTW + -72ACHISTW Combine like terms: 72ACHISTW + -72ACHISTW = 0 -72ACHISTW + 9C = 0 Factor out the Greatest Common Factor (GCF), '9C'. 9C(-8AHISTW + 1) = 0 Ignore the factor 9.Subproblem 1
Set the factor 'C' equal to zero and attempt to solve: Simplifying C = 0 Solving C = 0 Move all terms containing C to the left, all other terms to the right. Simplifying C = 0Subproblem 2
Set the factor '(-8AHISTW + 1)' equal to zero and attempt to solve: Simplifying -8AHISTW + 1 = 0 Reorder the terms: 1 + -8AHISTW = 0 Solving 1 + -8AHISTW = 0 Move all terms containing C to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -8AHISTW = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -8AHISTW = 0 + -1 -8AHISTW = 0 + -1 Combine like terms: 0 + -1 = -1 -8AHISTW = -1 Add '8AHISTW' to each side of the equation. -8AHISTW + 8AHISTW = -1 + 8AHISTW Combine like terms: -8AHISTW + 8AHISTW = 0 0 = -1 + 8AHISTW Simplifying 0 = -1 + 8AHISTW The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
C = {0}
| M=-8x+2z-6+3x-4z+3 | | 23(9+x)=-5(4-x) | | 6+2(16-1*6)= | | SolveT=M(3+FG)forG | | D=-2y+9x-9+4y-9x+6 | | x^2-7x+90=0 | | 1(2x-1)/33 | | (x^2+4)(x^2-1)=0 | | 3-2x=5-4x | | ln^2(x)=4x | | B=-3x+9y-5y+5x-4x+6y | | 12=4x+6 | | L=-9c+4b-8b+6c-3c+6b | | 9y-5=0 | | 10+2(2x-1)=16 | | (ln^2x)=4x | | (lnx^2)=4x | | 2x^2-60x=2x^2 | | W=-5c+3c-9+4 | | z+3(2-i)=5+i | | S=-5b-3b+6-7 | | x^2+x+2.5=0 | | D=-9c+6c-8c | | 64/x=4 | | A=-7y+6y | | 0.50x+0.25(30)=21.5 | | 50+(6x-2)=180 | | B=-9x-3x | | -14(2x-10)=28 | | 4a-3=15 | | 5x+5=8x-9 | | -5p+5+6p=10 |